RATIFIKASI STATUTA ROMA 1998 (ICC ) TERHADAP TEGAKNYA KEADILAN DALAM PERLINDUNGAN HAK ASASI MANUSIA DI INDONESIA - Bambang Purwanto (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
In this globalization era, cooperative relationships spread. The relationship between one country and another is as if no border. Problems arousing are also more complicated as the increas-ing of the people's needs. Law has very important roles in regulating those relationships. International law is crucially needed in maintaining harmonious relationships among people and countries. The Rome Statute is more than an international criminal law instrument, but it plays a strategic role in realizing the fulfillment of human rights. The provisions of the Rome Statute are not retroactive. Because the Rome Statute is more oriented to prevent the occurrence of gross human rights violations in the future. When the Rome Statute is ratified, it will improve and strengthen the national legal and human rights system.